Conceptual Design of the Production of Virgin Coconut Oil (VCO) Using Low-Pressure Oil Extraction That Employs Centrifugation Method - Pestaño, Lola Domnina; Bautista, Jolina Danielle; Sayson , Lans; Siat, Joshua Ladd (Challenges and Advances in Chemical Science Vol. 9, 2022)
Virgin Coconut Oil (VCO) is a product obtained from fresh coconut that has been very famous in the market due to its several uses. The research intends to investigate VCO technologies used for production that utilizes low-pressure oil extraction that employs centrifugation, determine all the recovered materials and wastes’ percent recovery by weight in the processing of VCO, and develop a conceptual design of the production of VCO that applies to a village-scale coconut community or farm in San Pablo, Laguna, Philippines. Preparation of raw materials includes splitting and grating of coconut meat. At a low pressure of 460 psi, the oil can be extracted from the dried grated coconut meat with 11% moisture content. However, this method alone will need at least two weeks for the crude coconut oil to settle. The centrifugation method can help lessen the settling time drastically. A conceptual design for the combined method that is applicable to a village-scale setting was developed based on the investigation of VCO processing technologies by applying the shortest drying time for the comminuted coconut meat to reach the desired moisture content in a tray dryer at 29.07 minutes at a drying temperature of 70\(^{°}\)C as predicted by the Laplace Transform Model. Oil from dried meat can be extracted using low pressure and at 2700 RPM and 60 minutes of centrifugation that produces the clearest oil with a yield of 92.84 % v/v and a recovery of 18.43%. The VCO produced is expected to qualify in the Asian and Pacific Coconut Community (APCC) VCO Standards. The weight of all recovered materials and wastes in the VCO processing technology were all accounted for using mass balance.